A bibliometric analysis of academic papers on frugal innovation - Rajnish Tiwari; Katharina Kalogerakis (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2016)
The term "frugal innovation" has established itself in scholarly discourse as well as in actual business practice in a short time. Nevertheless, its theoretical antecedents and underpinnings remain unclear. In this study we present results of a bibliometric analysis, which indicate that the present-day understanding of frugal innovation is shaped primarily by discourses on "bottom of the pyramid", "reverse innovation" and "disruptive innovation" and it has been targeted at "emerging economies". Even though rediscovery of frugality's virtue began in the developing world, it is spreading steadily to the economically developed world due to growing (global) demand for sustainable and affordable excellence. Frugal innovations are often associated with sustainability and development. Today, research on frugal innovations represents a very young and dynamic field: most scholarly publications and many of the references cited therein have been published in the past 5-6 years. Researchers would be, however, well-advised to incorporate insights on frugality and simplicity generated in other disciplines and other times, for example in the 1970s. Our study shows that the research on frugal innovations needs to take a calibrated, multidisciplinary approach.
Keywords: 330